The Goldmark case : an American libel trial - Dwyer, William L. (University of Washington Press, 1984)
The lawyer for the plaintiff describes the 1963 libel case of Washington State legislator John Goldmark--accused of being a communist--and probes the impact of this case on issues of civil liberties, communism and McCarthyism, the radical right, and trial by jury.